Biologia e tabela de vida de Tetranychus desertorum (Acari: Tetranychidae) sobre folhas de feijão (Phaseolus vulgaris) Biology and life table of Tetranychus desertorum (Acari: Tetranychidae) on leaves of kidney bean (Phaseolus vulgaris) - Edgar Rivero; Carlos Vásquez (Zoologia (Curitiba), 2009)
Biological aspects and life table of the red spider mite, Tetranychus desertorum Banks, 1900, were studied on leaf discs of kidney bean (Phaseolus vulgaris Linnaeus) cultivar "Tacarigua" under laboratory conditions (28 ± 2ºC, 70 ± 10% R.H. and 12:12h). Our results showed that total developmental time was 6.8 days for females, with partial duration of immature stages corresponding to 3.8, 1.4, 1.0 and 0.7 for egg, larva, protonymph and deutonymph, respectively. Preoviposition, oviposition and postoviposition periods were 1.1, 8.4 and 1.3 days, respectively; and the higher mean fecundity (6.93 eggs/female/day) was observed on day 4. Female mean longevity was 10 days. The life table parameters recorded were: net reproduction rate (Ro) = 41.10 individuals; generation time (T) = 11.15 days; intrinsic natural growth (r m) = 0.144 individuals/female/day, and finite natural increase rate (λ) = 1.155 individuals/female. Our findings could be a basis for further studies devoted to determine damage and control strategies for T. desertorum on kidney bean crops.